Effect of Cigarette Smoking on Patient-Reported Outcomes in Hip Arthroscopic Surgery: A Matched-Pair Controlled Study With a Minimum 2-Year Follow-up. Issue 1 (29th January 2019) - Lall, Ajay C.; Hammarstedt, Jon E.; Gupta, Asheesh G.; Laseter, Joseph R.; Mohr, Mitchell R.; Perets, Itay; Domb, Benjamin G.
Background: The rate of hip arthroscopic surgery has recently increased; however, there is limited literature examining patient-reported outcomes (PROs) in cigarette smokers. Purpose/Hypothesis: The purpose of this study was to evaluate whether smoking status for patients undergoing hip arthroscopic surgery affects clinical findings and PRO scores. We hypothesized that patients who smoke and undergo primary hip arthroscopic surgery will have similar clinical examination findings and preoperative and postoperative PRO scores compared with nonsmoking patients. Study Design: Cohort study; Level of evidence, 3. Methods: Data were collected on all patients who underwent primary hip arthroscopic surgery from February 2008 to July 2015. A retrospective analysis of the data was then conducted to identify patients who reported cigarette use at the time of the index procedure. Patients were matched 1:2 (smoking:nonsmoking) based on sex, age within 5 years, labral treatment (repair vs reconstruction vs debridement), workers' compensation status, and body mass index within 5 kg/m 2 . All patients were assessed preoperatively and postoperatively using 4 PRO measures: the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), Hip Outcome Score–Sport-Specific Subscale (HOS-SSS), and International Hip Outcome Tool–12 (iHOT-12). Pain was estimated using a visual analog scale. Satisfaction was measured on a scale from 0 to 10. Significance was set at P < .05. Results: A total of 75 hips were included in the smoking group, and 150 hips were included in the control group. Preoperatively, the smoking group had significantly lower PRO scores compared with the control group for the mHHS, NAHS, and HOS-SSS. Both groups demonstrated significant improvement from preoperative levels. A minimum 2-year follow-up was achieved, with a mean of 42.5 months for the smoking group and 47.6 months for the control group ( P = .07). At the latest follow-up, the smoking group reported inferior results for all outcome measures compared with controls. The improvement in PRO scores and rates of treatment failure, revision arthroscopic surgery, and complications was not statistically different between the groups. Conclusion: Patients who smoke had lower PRO scores preoperatively and at the latest follow-up compared with nonsmokers. Both groups demonstrated significant improvement in all PRO scores. These results show that while hip arthroscopic surgery may still yield clinical benefit in smokers, these patients may ultimately achieve an inferior functional status. To optimize results, physicians should advise patients to cease smoking before undergoing hip arthroscopic surgery.